Antagonistic Effect and Mechanism of Gabapentin on Neuropathic Pain in Rats through P38 MAPK Signaling Pathway - Jin, Qingsong; Li, Wei; Chu, Xiaoli; Huang, Lanji (Cellular and Molecular Biology, 2022)
The etiology of neuropathic pain is complex, and the patients are distressed. In order to master more accurate information in the treatment of human nerve tissue and improve the efficiency of treatment, this paper discusses the antagonistic effect of gabapentin on neuropathic pain in rats through the p38 MAPK signal pathway. Thirty-six female Sprague Dawley (SD) rats were randomly divided into three groups, 12 in each group. One group was spinal nerve ligation group (SNL group), gabapentin Group (GBP group, spinal nerve ligation and intraperitoneal injection of gabapentin (50 mg/kg)) and sham operation group (sham group, no spinal nerve ligation, other surgical procedures were the same as SNL group), At 1, 3, 5 and 7 days after operation, the paw contraction latency (TWL) and mechanical paw contraction threshold (MWT) were detected. Then, the expression of Toll-like receptor 4 (TLR4) in dorsal root ganglia was detected by SPSS statistical analysis. Compared with the sham group, MWT and TWL in the SNL group and GBP group were lower at each time point after the operation (all P < 0.05). MWT and TWL in the GBP group were higher than those in the SNL group at 5 and 7 days after the operation (all P < 0.05). In addition, compared with the sham group, the expression of TLR4 in the dorsal root ganglia of the SNL group was significantly increased (P < 0.05), while the expression of TLR4 in the GBP group was not significantly increased (P > 0.05). Compared with the SNL group, the expression of TLR4 in the dorsal root ganglion of the GBP group was significantly decreased (P < 0.05). Thus, gabapentin combined therapy can effectively reduce the degree of pain in patients with significant efficacy, high safety and fewer adverse reactions.